Ti-superoxide catalyzed oxidative amidation of aldehydes with saccharin as nitrogen source: synthesis of primary amides - Kamble, Rohit B.; Mane, Kishor D.; Rupanawar, Bapurao D.; Korekar, Pranjal; Sudalai, A.; Suryavanshi, Gurunath (RSC Advances, 2020)
A new heterogeneous catalytic system (Ti-superoxide/saccharin/TBHP) has been developed that efficiently catalyzes oxidative amidation of aldehydes to produce various primary amides. The protocol employs saccharin as amine source and was found to tolerate a wide range of substrates with different functional groups. Moderate to excellent yields, catalyst reusability and operational simplicity are the main highlights. A possible mechanism and the role of the catalyst in oxidative amidation have also been discussed.